2008
DOI: 10.1097/wnr.0b013e3282f97b64
|View full text |Cite
|
Sign up to set email alerts
|

Methadone: does it really have low efficacy at μ-opioid receptors?

Abstract: There is confusion in the literature concerning the relative agonist efficacy of methadone at micro-opioid receptors (MOPrs). Here, we confirm that methadone is a full agonist in guanosine 5'-O-[gamma-thio]triphosphate (GTPgammaS) binding studies. Methadone, however, seems to have low efficacy in studies of MOPr activation of G-protein-gated potassium (GIRK) channels, but this is because it directly inhibits the GIRK channels. Methadone also inhibits alpha2-adrenoceptor-activated GIRK channels. Methadone is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
0
15
2
Order By: Relevance
“…Many studies have reported the endomorphins as being partial agonists, 18,21 whereas methadone has been reported to be an agonist with a similar efficacy to DAMGO. 11,22,23 The most likely explanation for the discrepancy in our study is that methadone appeared to have a reduced maximal effect because of its propensity to block K channels, including the GIRK channels likely to contribute to the hyperpolarization measured in the present study. 22,24 Conversely, the observation that the maximum effect of the endomorphins was similar to that of well-recognized high-efficacy agonists suggests the presence of some spare receptors in our system, as noted previously with similar cell lines.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Many studies have reported the endomorphins as being partial agonists, 18,21 whereas methadone has been reported to be an agonist with a similar efficacy to DAMGO. 11,22,23 The most likely explanation for the discrepancy in our study is that methadone appeared to have a reduced maximal effect because of its propensity to block K channels, including the GIRK channels likely to contribute to the hyperpolarization measured in the present study. 22,24 Conversely, the observation that the maximum effect of the endomorphins was similar to that of well-recognized high-efficacy agonists suggests the presence of some spare receptors in our system, as noted previously with similar cell lines.…”
Section: Discussioncontrasting
confidence: 66%
“…11,22,23 The most likely explanation for the discrepancy in our study is that methadone appeared to have a reduced maximal effect because of its propensity to block K channels, including the GIRK channels likely to contribute to the hyperpolarization measured in the present study. 22,24 Conversely, the observation that the maximum effect of the endomorphins was similar to that of well-recognized high-efficacy agonists suggests the presence of some spare receptors in our system, as noted previously with similar cell lines. 11 It is also possible that the efficacy discrepancies reflect subtle bias in ligand signaling to one pathway over another in different tissues, and it is worth noting that endomorphins have recently been reported to show such bias in assays of β-arrestin recruitment.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…HEK293 cells were maintained at 37°C in 95% O 2 , 5% CO 2 , in Dulbecco's modified Eagle's medium (Invitrogen, Carlsbad, CA) supplemented with 10% fetal bovine serum, 10 U/ml penicillin, and 10 mg/ml streptomycin. In addition, the culture medium for the HEK293 cells stably expressing T7-tagged MOPr (Bailey et al, 2003;Rodriguez-Martin et al, 2008) contained 250 g/ml G-418 (Geneticin), a selective antibiotic (PAA, Pasching, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to 5-HT 3 receptors, methadone directly interacts with several other ion channels, including hERG K ϩ channels (Katchman et al, 2002;Eap et al, 2007), inwardly rectifying K ϩ channels (Rodriguez-Martin et al, 2008), the NMDA subtype of the glutamate receptor (Ebert et al, 1995;Callahan et al, 2004), and the ␣3␤4 and ␣7 nicotinic receptors (Xiao et al, 2001;Pakkanen et al, 2005). (R)-Methadone, the isomer that preferentially binds to -opioid receptors is also more potent than (S)-methadone as an inhibitor of NMDA receptors (Kristensen et al, Callahan et al, 2004), whereas (S)-methadone has a higher potency than (R)-methadone as an inhibitor of hERG channels (Eap et al, 2007).…”
Section: Discussionmentioning
confidence: 99%